Evaluation of cell culture‐grown Bartonella antigens in immunofluorescent antibody assays for the serological diagnosis of bartonellosis in dogs. (11th October 2018) - Neupane, Pradeep; Hegarty, Barbara C.; Marr, Henry S.; Maggi, Ricardo G.; Birkenheuer, Adam J.; Breitschwerdt, Edward B.
Abstract : Background: Because of poor sensitivity and questionable specificity of immunofluorescent antibody assays (IFAs), serological diagnosis of Bartonella species infections in dogs remains challenging. Despite limitations, IFA testing is the historical "gold standard" for Bartonella serodiagnosis in animals and humans. Because most diagnostic laboratories test against only 1 or 2 Bartonella spp., testing against a broader panel of Bartonella antigens may enhance diagnostic sensitivity and specificity. Objective: To evaluate the sensitivity and specificity of Bartonella IFA using 8 cell culture‐grown Bartonella spp. isolates. Animals: Archived serum samples from 34 Bartonella spp. naturally exposed, polymerase chain reaction (PCR)‐positive dogs and from 26 PCR‐negative and IFA‐negative dogs. Methods: Bartonella IFA sensitivity and specificity were assessed using cell culture‐grown whole cell antigens derived from 3 Bartonella henselae ( Bh ) strains ( Bh Houston 1, Bh San Antonio Type 2, Bh California 1), 3 Bartonella vinsonii subsp. berkhoffii genotypes ( Bvb I, II, and III), Bartonella koehlerae ( Bk ), and Bartonella quintana ( Bq ). Results: Only 62% of 34 Bartonella spp. PCR‐positive dogs were seroreactive to any of the 8 Bartonella IFA antigens, indicating low IFA sensitivity. PCR‐positive dogs were most often IFA seroreactive to Bq ( n = 15), to Bvb II ( n = 13), or to both ( n = 9) antigens. Of the 26 previously IFA‐negative/PCR‐negative dogs, 4 (15%) were seroreactive using the expanded antigen panel. Conclusion and Clinical Importance: Despite IFA testing of dogs against 8 different Bartonella isolates, IFA sensitivity remained poor, and specificity was only 85%. Development of a reliable serological assay is needed to facilitate the diagnosis of Bartonella infection in dogs.